Applications of fly ash for CO2 capture, utilization, and storage. (January 2019) - Dindi, Abdallah; Quang, Dang Viet; Vega, Lourdes F.; Nashef, Enas; Abu-Zahra, Mohammad R.M.
Highlights: The hazards of fly ash to the environment and public health are outlined. Fly ash has a great potential for capture, utilization, and storage of CO2 (CCUS) applications. Fly ash based adsorbents have comparable performances with commercial adsorbents when applied for CO2 capture. CO2 utilization using fly ashes can produce valubale products. New pathways for applying fly ash in CO2 utilization are introduced and discussed. Abstract: Utilization is one of the prominent strategies for the management of hazardous industrial wastes like fly ash. As fossil-based power is expected to remain a major source of global electricity supply in the coming years, the absence of effective management strategies will exacerbate the problem of fly ash waste in the environment. Global fly ash utilization rates remain low due to limited utilization opportunities outside the construction industry. This necessitates the development of new pathways for its utilization as a means of diverting it from landfills where it poses a significant threat to the environment. Carbon capture, utilization, and storage presents opportunities to utilize fly ash in various ways; as a capture material, as a medium for permanent CO2 storage via mineralization, and as a catalyst or catalyst support for CO2 utilization processes. This study reviews the different technologies through which fly ash and materials derived from fly ash are applied in the CO2 capture, utilization, and storage technology while highlighting some challenges and opportunities for further research and development.